2016
DOI: 10.1126/science.aaf5023
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure of Hsp90-Cdc37-Cdk4 reveals that Hsp90 traps and stabilizes an unfolded kinase

Abstract: The Hsp90 molecular chaperone and its Cdc37 co-chaperone help stabilize and activate over half of the human kinome. However, neither the mechanism by which these chaperones assist their client kinases nor why some kinases are addicted to Hsp90 while closely related family members are independent is known. Missing has been any structural understanding of these interactions, with no full-length structures of human Hsp90, Cdc37 or either of these proteins with a kinase. Here we report a 3.9Å cryoEM structure of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
516
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(548 citation statements)
references
References 56 publications
(41 reference statements)
29
516
1
2
Order By: Relevance
“…In general, the conformational landscape of the kinase is reshaped by the presence of the oncogenic mutations, which led to a less compact structure of regions that may specifically interact with Hsp90-Cdc37, especially the β1-β5-strands and the P-loop, supporting previous studies that suggested a correlation between Hsp90 binding and the openness of the kinase fold174041. Moreover, in the pY416-activated state of c-Src3MΔC, we found an even more extended kinase structure that may increase the interaction with Hsp90 and Cdc37.…”
Section: Discussionsupporting
confidence: 80%
“…In general, the conformational landscape of the kinase is reshaped by the presence of the oncogenic mutations, which led to a less compact structure of regions that may specifically interact with Hsp90-Cdc37, especially the β1-β5-strands and the P-loop, supporting previous studies that suggested a correlation between Hsp90 binding and the openness of the kinase fold174041. Moreover, in the pY416-activated state of c-Src3MΔC, we found an even more extended kinase structure that may increase the interaction with Hsp90 and Cdc37.…”
Section: Discussionsupporting
confidence: 80%
“…iii) In addition to a decreased steady-state level of the Hsc82 (Hsp90) protein in naa10Δ cells (see item ii above), one would also expect the impairment of the Hsp90 system as a whole in the absence of NatA. The functioning of Hsp90 involves its transient binding to cochaperones, with some of them carrying bound clients (12). Given the role of Nt-Ac groups in modulating (usually enhancing) protein interactions within cognate protein complexes (49), decreased affinities among most components of the Hsp90 system, which are not Nt-acetylated in naa10Δ cells, would be expected to perturb both the delivery of clients to Hsp90 by cochaperones and other aspects of this circuit, based on transient protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cochaperones of the ∼90-kDa Hsp90 comprise, in mammals, ∼30 distinct proteins. They participate in the delivery of clients to Hsp90 and contribute to related processes, including ATP hydrolysis by Hsp90 (12). Because of its ability to modulate protein conformations, the Hsp90 system can either exacerbate or counteract the fitness-reducing effects of mutations in cellular proteins.…”
mentioning
confidence: 99%
“…While this article was in print the cryo-EM structure of the Hsp90-Cdc37-Cdk4 complex was published showing that Cdc37-phosphoSer13 contributes towards the coordination of a specific conformation of the Cdc37 N-terminal domain and its position relative to Hsp90 (39). This structure further supports our conclusion that a structural change is required for PP5-mediated dephosphorylation of Cdc37 in the context of the clientloaded Hsp90 chaperone complex and that this may be the trigger for client kinase release from the Hsp90-chaperone complex.…”
Section: Methodsmentioning
confidence: 99%